Do Independent Director Departures Predict Future Bad Events?. (2nd February 2017) - Fahlenbrach, Rüdiger; Low, Angie; Stulz, René M.
Abstract : Following surprise independent director departures, affected firms have worse stock and operating performance, are more likely to restate earnings, face shareholder litigation, suffer from an extreme negative return event, and make worse mergers and acquisitions. The announcement returns to surprise director departures are negative, suggesting that the market infers bad news from surprise departures. We use exogenous variation in independent director departures triggered by director deaths to test whether surprise independent director departures cause these negative outcomes or whether an anticipation of negative outcomes is responsible for the surprise director departure. Our evidence is more consistent with the latter. Received January 12, 2016; editorial decision October 7, 2016 by Editor David Denis.